MOV10 Helicase Interacts with Coronavirus Nucleocapsid Protein and Has Antiviral Activity - Li Wang (American Society for Microbiology, 2021)
Coronaviruses (CoVs) are emerging pathogens causing life-threatening diseases in humans. Knowledge of virus-host interactions and viral subversion mechanisms of host pathways is required for the development of effective countermeasures against CoVs.